2008
DOI: 10.1074/jbc.m710089200
|View full text |Cite
|
Sign up to set email alerts
|

Select Paramyxoviral V Proteins Inhibit IRF3 Activation by Acting as Alternative Substrates for Inhibitor of κB Kinase ϵ (IKKe)/TBK1

Abstract: V accessory proteins from Paramyxoviruses are important in viral evasion of the innate immune response. Here, using a cell survival assay that identifies both inhibitors and activators of interferon regulatory factor 3 (IRF3)-mediated gene induction, we identified select paramyxoviral V proteins that inhibited double-stranded RNA-mediated signaling; these are encoded by mumps virus (MuV), human parainfluenza virus 2 (hPIV2), and parainfluenza virus 5 (PIV5), all members of the genus Rubulavirus. We showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 41 publications
(49 reference statements)
3
71
3
Order By: Relevance
“…MV replicates in the cytoplasm and activates the RIG-I sensor due to the presence of cytosolic 5Ј-triphosphate-containing viral transcripts (24,25), but paradoxically, the V protein of MV blocks the mda-5 sensor of the RLR IFN-␤ induction pathway (6,18). Furthermore, TLR3 signaling through the adapter TRIF is impaired by V proteins of rubulaviruses but not by the MV V protein (14). Both the cytoplasmic RLRs and membrane-bound TLR3 act as sensors of viral dsRNA to initiate the innate immune response and IFN induction.…”
Section: Irf-3 Phosphorylation Is Enhanced In C Ko -Infected Comparedmentioning
confidence: 99%
“…MV replicates in the cytoplasm and activates the RIG-I sensor due to the presence of cytosolic 5Ј-triphosphate-containing viral transcripts (24,25), but paradoxically, the V protein of MV blocks the mda-5 sensor of the RLR IFN-␤ induction pathway (6,18). Furthermore, TLR3 signaling through the adapter TRIF is impaired by V proteins of rubulaviruses but not by the MV V protein (14). Both the cytoplasmic RLRs and membrane-bound TLR3 act as sensors of viral dsRNA to initiate the innate immune response and IFN induction.…”
Section: Irf-3 Phosphorylation Is Enhanced In C Ko -Infected Comparedmentioning
confidence: 99%
“…This raises the possibility that paramyxoviruses have other mechanisms to block signaling responses through RIG-I. In this context, it has recently been reported that SeV-C can block RIG-I (28) and that some paramyxovirus V proteins, including PIV5-V, can block IRF-3 phosphorylation by interacting with IKKε/TBK1 and acting as alternative substrates (16). The latter phenomenon is presumably cell type specific, since we have failed to observe the expected inhibition of RIG-I by PIV5-V (2), and furthermore PIV5-V does not block induction by overexpression of the CARD domains of mda-5 or IPS-1 (Fig.…”
Section: Vol 83 2009 Mda-5 Inhibition By Paramyxovirus V Proteins 1471mentioning
confidence: 99%
“…Rubulaviruses including MuV, hPIV2, and PIV5 use V protein as a decoy substrate for the IRF-3 kinases TANK-binding kinase 1 (TBK-1) and inhibitor of NF-κB kinase (IKK)e (Figure 3), both inhibiting phosphorylation of IRF-3 and facilitating IKKe/TBK-1 polyubiquitination and degradation to prevent further signalling [81] . Henipavirus V proteins do not cause IKKe/TBK-1 degradation [81] or block TLR-3/IRF-3 dependent signalling [76,81] . For henipaviruses, this appears to be a function of the W protein, as NiV W, although having no effect on MDA5 signalling, inhibited TLR-3-dependent phosphorylation of IRF-3 [82] .…”
Section: Inhibition Of Irf-3 Activationmentioning
confidence: 99%